2011
DOI: 10.1111/j.1464-5491.2010.03197.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of tendons in patients with diabetes mellitus: a systematic review

Abstract: All the articles indicated some relation between diabetes mellitus and tendon alterations in human beings, but due to methodological drawbacks, this association could not be sustained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…All these studies presented abnormal changes of the thickness and structure of collagen fibers in diabetic tendons, although the association between diabetes mellitus and tendon alterations could not be sustained due to methodological drawbacks [11]. However, all the studies reported the increasing trend of thickening tendons in diabetic patients.…”
Section: Imaging Findingsmentioning
confidence: 96%
See 2 more Smart Citations
“…All these studies presented abnormal changes of the thickness and structure of collagen fibers in diabetic tendons, although the association between diabetes mellitus and tendon alterations could not be sustained due to methodological drawbacks [11]. However, all the studies reported the increasing trend of thickening tendons in diabetic patients.…”
Section: Imaging Findingsmentioning
confidence: 96%
“…However, not all the patients with DM are symptomatic, some of them are asymptomatic, even with an increased thickness or structural abnormalities in supraspinatus and biceps tendons and Achilles tendons found with imaging exams [11]. It is suggested that the insensitive neuropathy may reduce or even block the transmission of pain signal, thus leading to asymptomatic conditions in some patients with DM [21].…”
Section: Clinical Manifestation Of Tendon Pathologies In Diabetic Patmentioning
confidence: 98%
See 1 more Smart Citation
“…This study presents, to the best of the authors' knowledge, the first attempt to correlate biomarkers as factors of good prognosis to the evolution of the recovery. Hyperglycemia and especially type II diabetes, leads to a disorganization of collagen fibers, and an increase in tendons thickness and volume [20] ; hyperthyroidism increases collagen catabolism and hypothyroidism leads to a decreased collagen metabolism [21]; hypercholesterolemia impairs the tendon extra cell matrix and thus alters its biomechanical properties [22] and finally, hyperucemia could cause an inflammation provoking the degeneration of the tendon tissue [23]. It might then be surprising that no correlation was found between the values of the biological markers and the evolution of the tendons healing evaluated by the VAS and the algometer.…”
Section: Are There Biologic Factors Of Good Prognosis After a Platelementioning
confidence: 99%
“…The mechanism by which diabetes acts on the structure of the collagen of tendons has not been fully understood yet 1,[4][5][6][7] . However, there is evidence that hyperglycemia can cause an accelerated process of nonenzymatic glycation and deposition of collagen in a disorganized form in periarticular connective tissues 6,8,9 .…”
Section: Introductionmentioning
confidence: 99%